2001
DOI: 10.1161/01.cir.103.23.2816
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary Stenting and Angiographic Results

Abstract: The use of a thinner-strut device is associated with a significant reduction of angiographic and clinical restenosis after coronary artery stenting. These findings may have relevant implications for the currently most widely used percutaneous coronary intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
167
2
8

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 723 publications
(185 citation statements)
references
References 27 publications
8
167
2
8
Order By: Relevance
“…The ISAR-STEREO-I and ISAR-STEREO-II trials were large-scale clinical studies carried out by Pache et al in 2003, respectively, in which over 600 patients were randomly assigned to receive either a thin (0.05 mm) or thick (0.13-0.14 mm) strut stent for the treatment of symptomatic coronary heart disease. 40,68 At 6 month follow-up in both trials, the incidence of angiographic in-stent restenosis was significantly higher (p < 0.05) for patients treated with the thick strut stents. Based on these results, it was concluded that strut thickness has a major impact on the clinical outcome following coronary stent deployment.…”
Section: Discussionmentioning
confidence: 92%
“…The ISAR-STEREO-I and ISAR-STEREO-II trials were large-scale clinical studies carried out by Pache et al in 2003, respectively, in which over 600 patients were randomly assigned to receive either a thin (0.05 mm) or thick (0.13-0.14 mm) strut stent for the treatment of symptomatic coronary heart disease. 40,68 At 6 month follow-up in both trials, the incidence of angiographic in-stent restenosis was significantly higher (p < 0.05) for patients treated with the thick strut stents. Based on these results, it was concluded that strut thickness has a major impact on the clinical outcome following coronary stent deployment.…”
Section: Discussionmentioning
confidence: 92%
“…The finite element models of the stents were generated and meshed in ANSYS (Canonsburg, PA, USA) and were generated based on the stents used in the ISAR STEREO Trial, namely the ACS RX MultiLink and the ACS MultiLink RX Duet [12]. Both stents are manufactured by the same company, namely Guidant/Advanced Cardiovascular Systems.…”
Section: Model Geometrymentioning
confidence: 99%
“…In recent years, several clinical trials have identified stent strut thickness as an independent predictor of restenosis [2,12,23]. A clear conclusion from the many clinical studies on stent strut thickness is that stents with thinner struts have a lower restenosis rate, consequently, most of the current generation of stents are produced with thinner struts using high strength materials such as cobalt-chromium alloys [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os resultados obtidos após implante de stents são sobremaneira influenciados por sua configuração e arquitetura [3][4][5] , material utilizado para recobrir sua superfície 6 e espessura de suas hastes 5,7,8 . Ademais, comparações entre stents auto-expansíveis e balão-expansíveis têm demonstrado as vantagens da necessidade de menores pressões de insuflação dos primeiros, com taxas de reestenose angiográfica e clínica semelhantes entre os dois tipos de dispositivos, mas menor incidência de injúria e dissecção de bordos com os stents auto-expansíveis 9 .…”
unclassified